There's a monster in my fridge - Hart, Caryl; Allwright, Deborah (Hauppauge, New York : Barron's Educational Series, 2016)
Monsters, monsters, everywhere--but not as scary as you think! Each turn of the fun split-page in this book is filled with super-silly monsters. There are lots of giggle-worthy revelations for children--including one at the very end that puts them right in the middle of the action.
Keywords: Children's stories